Arduino-based light source used to demonstrate mixing of colors and as a simple system for luminescence observations. (4th February 2019) - Bazak, Jerzy; Szewczyk, Grzegorz
Abstract: Additive light mixing can be hard to describe without a proper example. We describe a simple, portable device for demonstration purposes. Its advantage is the use of a RGB diode, which can generate light of variable wavelengths. It may be used to demonstrate principles of color mixing and light penetrating through a tissue, also different kinds of luminescence. Our custom-designed box is 3D printable, allowing for easy reproduction or modification and can be powered by portable power source.